Coping and health status predicts PTSD 12 months after a serious motor vehicle accident - Pires, Tânia Sofia Fernandes (2011)
Background: Maladjusted coping strategies after motor vehicle accidents (MVA) can contribute to the development of psychological symptoms, as PTSD. Methods: Measures of Acute Stress Disorder, PTSD scale, Coping, Social Support and physical health were used to evaluate 101MVA victims with serious injuries 5 days, 4 and 12 months after the accident Findings: 67% of the participants had ASD (T1), 58% had PTSD at T2 and 47% had PTSD at T3. Victims that report more general coping strategies, a mix of adequate and inadequate strategies, report more ASD symptoms, and more PTSD symptoms. At T3 health problems and lower social support, are related to PTSD, and regression analysis showed that general coping and health symptoms are predictors of PTSD. Discussion: Victims with serious health problems should be screening for psychological symptoms, and professionals should help victims to improve adjusted strategies to cope with the impact of MVA.